Are YouTube Videos Sufficient for Educational Purposes for Robotic Right Hemicolectomy Learning and Has Complete Mesocolic Excision Changed That? - Bal, Ali; Çolakoğlu, Muhammet Kadri; Öter, Volkan; Pişkin, Erol; Bostancı, Erdal Birol (Turkish Journal of Gastroenterology, 2023)
Background/Aims: The aim of this study is to evaluate the efficiency for educational purposes by evaluating the videos published on YouTube channel, which is an open source video sharing platform, for robotic right hemicolectomy procedure. Materials and Methods: We searched YouTube website to choose video clips that included information about robotic right hemicolec- tomy for right colon cancer. All videos were analyzed according to the criteria like quality of videos, quality of teaching, and modified Laparoscopic Surgery Video Educational Guidelines. Results: There were 16 complete mesocolic excision and 56 noncomplete mesocolic excision videos in the study. According to the Likert scale, calculated complete mesocolic excision scores were analyzed better than the noncomplete mesocolic excision group and this difference was statistically significant (P < .0001). The teaching quality scores of complete mesocolic excision videos were higher than noncomplete mesocolic excision group and this result was statistically significant (P = .02). The videos were scored according to the modified Laparoscopic Surgery Video Educational Guideline, and the score difference was statistically significant between complete mesocolic excision and noncomplete mesocolic excision videos (P < .001). The video power index was higher (mean 5.52 ± 15.56 vs. mean 1.66 ± 3.41) in the complete mesocolic excision group, but there was no statistically significant difference between the 2 groups (P = .086). Conclusions: Most of the robotic right hemicolectomy videos on the YouTube platform are insufficient in terms of educational capaci- ties. Complete mesocolic excision-containing videos are slightly superior in this respect to noncomplete mesocolic excision videos, as considering a new technique can make video presenters more attentive. In our opinion, if the images presented to the video platforms are to be used for educational purposes, they must undergo a certain evaluation and screening process.